2011
DOI: 10.1111/j.1750-3841.2010.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Heating during Alkaline‐Cooking of Aflatoxin Contaminated Maize

Abstract: The potential presence of aflatoxins in maize destined for human consumption is a serious problem to the Mexican food supply, as these toxic compounds may persist during the traditional alkaline-process for tortilla elaboration. Consequently, new detoxification procedures are needed that eliminate or at least minimize the aflatoxin risk, through lowering aflatoxin concentration in maize-based products. Under these considerations, the use of MTMP is recommended, since it has definite advantages including non-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Higher decomposition levels can be obtained by cooking at 230 to 300°C. 28 Pérez-Flores et al 29 used 270°C for 15 seconds to cook flattened maize-dough containing 69.62 ng AFB1/g, only 58% reduction in AFB 1 content was achieved (the pH of the maize-dough was 8.2). It is important to mention that temperatures above 150°C reduce the sensorial quality of the tortillas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher decomposition levels can be obtained by cooking at 230 to 300°C. 28 Pérez-Flores et al 29 used 270°C for 15 seconds to cook flattened maize-dough containing 69.62 ng AFB1/g, only 58% reduction in AFB 1 content was achieved (the pH of the maize-dough was 8.2). It is important to mention that temperatures above 150°C reduce the sensorial quality of the tortillas.…”
mentioning
confidence: 99%
“…Three rinses produce a less alkaline maize-dough, Perez-Flores and colleagues 29 had suggested that higher amounts of lime should be used to obtain more alkaline maize-dough. However, addition of 1% lime and subsequent rinsing once with tap water produces a maize-dough with a pH about 10.2.…”
mentioning
confidence: 99%
“…Pérez-Flores et al evaluated the effectiveness of maize detoxification achieved with a modified tortilla-making process in which maize grits are mixed with water and lime, cooked in a microwave oven, steeped, and then milled to obtain the fresh masa able to make tortillas. This method led until to 84% decrease in AFB1 content [24].…”
Section: Aflatoxinsmentioning
confidence: 99%
“…Therefore, most of the processing steps during food production such as temperatures below 250 o C have little or no www.intechopen.com effect on their content, which may lead to contaminated finished cereal based products. However, there are some other processing steps such as alkaline cooking, nixtamalization (tortilla process), extrusion, roasting, flaking and modified processing methods that may reduce the aflatoxin content, but cannot eliminate the aflatoxin completely (Arzandeh & Jinap, 2011;Bullerman & Bianchini, 2007;Park, 2002;Perez-Flores, Moreno-Martinez, & Mendez-Albores, 2011;Yazdanpanah, Mohammadi, Abouhossain, & Cheraghali, 2005). Physical sorting is also another effective measure in the reduction of aflatoxins, as high as 40-80% (Bullerman & Bianchini, 2007).…”
Section: Fate Of Aflatoxins During Processingmentioning
confidence: 99%